(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The study aims to justify the educational potential of juvenile media, identifying methods of fostering values of adolescents and youth of generation Z in the process of creating media materials. Based on the comparative analysis and questionnaire survey conducted to meet the study’ aims, it is concluded that the educational potential of juvenile media is based on the correspondence between the functions of juvenile media and the functions of the pedagogical process: educational (juvenile media) and teaching (pedagogical process); communicative and, accordingly, educational; creative and developing. In the pedagogical process, it is possible to implement the game function of juvenile media to solve the problems of professional and personal self-determination and to purposefully smooth out the risks associated with implementing the information/propaganda function of juvenile media. Juvenile media are the optimal environment for fostering values of modern adolescents and young people (generation Z) because they rely on their willingness to work with any information (find, transmit, create) and comprehend global problems; help to learn how to work painstakingly and bring things to an end, to remember important facts and patterns for the community.